Perancangan Sistem Basis Data Profil Mahasiswa Pada Sistem Informasi Mahasiswa Politeknik Piksi Ganesha - Riyansyah, Andri Taufiq; Pasaribu, Johni S (LPPM STMIK IKMI Cirebon, 2024)
The purpose of the database design for student profiles in Student Iformatio Systems at Polytehcic Piksi Ganesha is to simplify data management ad storage of studet information from the beginning to the end of their study period. To this goal, the collection of software needs is carried out through observations and interviews with relevant parties such as the Academic Division, lecturers, and students. The main achievement of Student Information Systems is to design a database that focuses on student data and profile. Waterfall methods are used in the design of these systems to ensure regularity and to form the foundation for further development that may have higher complexity. The utilities used include Visual Studio Code, XAMPP, and MySQL. The implementation is done using PHP-based web technology and Tailwind as a programming language and interface design. With this information system, it is expected that student data management at Polytechnic Piksi Ganesha will be more efficient and well organized.